2007
DOI: 10.1074/jbc.m700591200
|View full text |Cite
|
Sign up to set email alerts
|

The Size Exclusion Characteristics of Type I Collagen

Abstract: The mineral in bone is located primarily within the collagen fibril, and during mineralization the fibril is formed first and then water within the fibril is replaced with mineral. The collagen fibril therefore provides the aqueous compartment in which mineral grows. Although knowledge of the size of molecules that can diffuse into the fibril to affect crystal growth is critical to understanding the mechanism of bone mineralization, there have been as yet no studies on the size exclusion properties of the coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
113
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 219 publications
(123 citation statements)
references
References 43 publications
2
113
0
Order By: Relevance
“…We had previously hypothesized that calcification inhibitors that are small enough to penetrate the collagen fibril will prevent mineral growth inside the fibril, not selectively calcify the fibril (9). We tested this hypothesis using bone Gla protein (BGP; osteocalcin), a 6-kDa inhibitor of apatite growth (32) that is able to rapidly penetrate all of the water within the collagen FIGURE 4.…”
Section: Determination Of the Amount Of Mineral That Can Be Depositedmentioning
confidence: 99%
See 4 more Smart Citations
“…We had previously hypothesized that calcification inhibitors that are small enough to penetrate the collagen fibril will prevent mineral growth inside the fibril, not selectively calcify the fibril (9). We tested this hypothesis using bone Gla protein (BGP; osteocalcin), a 6-kDa inhibitor of apatite growth (32) that is able to rapidly penetrate all of the water within the collagen FIGURE 4.…”
Section: Determination Of the Amount Of Mineral That Can Be Depositedmentioning
confidence: 99%
“…We have suggested that large inhibitors of apatite growth can paradoxically favor mineralization within the fibril by selectively preventing apatite growth in the solution outside of the fibril (9). We have also proposed that large nucleators of apatite formation may generate small crystals outside the collagen fibril and that some of these crystals can subsequently diffuse into the fibril and grow (9).…”
mentioning
confidence: 99%
See 3 more Smart Citations